2020
DOI: 10.1002/ptr.6731
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tea consumption on metabolic syndrome: A systematic review and meta‐analysis of randomized clinical trials

Abstract: The metabolic syndrome (MetS) is one of the major health hazards and an epidemic worldwide. There is no known best remedy has been defined yet. In the current investigation, we designed a meta-analysis of randomized clinical trials (RCTs) to evaluate the beneficial effects of tea consumption in alleviating metabolic syndromes. Herein, we accumulated the relevant literature available on PubMed and EMBASE databases from January, 2000 to August, 2019. RCTs bearing impact factor of at least 1 or more were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
1
22
1
Order By: Relevance
“…Regarding the null results on diabetes, we may hypothesize that doses of coffee might not be sufficient to reduce the risk as reported in the scientific literature, or unmeasured confounding factors (i.e., the use of sugar in coffee) might counteract its beneficial effects on insulin sensitivity and glucose homeostasis. Regarding tea, summary of evidence showed it does not appear to significantly affect blood pressure or lipids in short-term [49], while data on metabolic outcomes are mixed and seems to potentially depend on type of tea and doses (i.e., associations observed for higher intake than those reported in our study, which may explain lack of significant findings) [16,50].…”
Section: Discussioncontrasting
confidence: 61%
“…Regarding the null results on diabetes, we may hypothesize that doses of coffee might not be sufficient to reduce the risk as reported in the scientific literature, or unmeasured confounding factors (i.e., the use of sugar in coffee) might counteract its beneficial effects on insulin sensitivity and glucose homeostasis. Regarding tea, summary of evidence showed it does not appear to significantly affect blood pressure or lipids in short-term [49], while data on metabolic outcomes are mixed and seems to potentially depend on type of tea and doses (i.e., associations observed for higher intake than those reported in our study, which may explain lack of significant findings) [16,50].…”
Section: Discussioncontrasting
confidence: 61%
“…Xu et al found a significant decrease in total cholesterol among normal weight, overweight, and obese individuals (combined) who consumed green tea vs. placebo (weighted mean difference [WMD]: −4.66 mg/dL; 95% CI: 6.36 to −2.96; p = .0001) in a random effects meta-analysis [ 31 ]. The remaining nine older systematic reviews found no significant effects on total cholesterol across various populations [ 3 , 11 , 18 , 19 , 22 , 27 , 30 , 34 , 49 ], which may be due to a smaller number of studies and overall sample size. The quality of these systematic reviews was judged to be low to high ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…No effects were reported for black tea vs. placebo [ 24 ]. Liu et al found a significant decrease in LDL cholesterol among individuals with metabolic syndrome who consumed green and black tea (combined) vs. placebo in a random effects meta-analysis (SMD: −0.63 mmol/L; 95% CI: −1.06 to −0.20; p = .0057) [ 30 ]. Xu et al found a significant decrease in LDL cholesterol among normal weight, overweight, and obese individuals (combined) who consumed green tea vs. placebo (WMD: −4.55 mg/dL; 95% CI: −6.31 to −2.80 mg/dL; p = .0001) in a random effects meta-analysis [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations